Intelligent robotic system for home services (design of mechanical system) - Chin, Chorng Hann. (2010)
This project is to design and build a domestic helper which is able to help provide assistances to human for instance helping an elderly get drinks from the fridge or getting books from a high level shelf. The robot that the author and his group are building is called DoCaRo-I. It is designed to serve tasks such as following a person by recognising his/her face, recognising human's speech ,serving drinks to guests in a party etc.The author objective and aim is to design the mechanical system & control of the DoCaRo-I. The first approach in design is to research different types of electronic domestic helper in the market, then from the research, a set of design requirements and specifications are specified. With the determined requirements and specifications, the author will be able to start designing. The author make used of morphological chart to help him design a few conceptual designs. Evaluation criteria is then used to analysis all the conceptual designs and the conceptual with the highest score will be chosen as the selected design. After which, calculations on the payload is done so as to chose the respective motors and size of the robot. With the calculations done, the selected design is then developed using CAD/CAM software: SolidWorks 2010. In this CAD/CAM software, the author is able to see all the constraints and stresses that might pose a problem in the finished product. After analysing, the author will then able to produce the detail design with dimensioning so that he is able to send for fabrication.